The Labor Market Earnings of Veterans: Is Military Experience More or Less Valuable than Civilian Experience? - Christos A. Makridis; Barry Hirsch (Institute of Labor Economics (IZA), 2021)
We assess the labor market experiences of military veterans, focusing on three major outcomes, among others, controlling for a wide array of demographic characteristics and industry and occupational fixed effects. First, we find that male and female veterans receive civilian earnings nearly equivalent to nonveteran men and women. This finding implies that military experience is valued in the labor market similarly to foregone civilian experience. Second, veterans are clustered in occupations with somewhat lower than average employment and real earnings growth, and in metropolitan areas with lower levels and growth of real GDP per capita. Third, veterans experience lower returns to formal educational investments (e.g., college) than do nonveterans. Veterans realize earnings gains from professional licenses, but their returns are lower than for nonveterans. These gains are concentrated among science, technology, engineering, and math (STEM) jobs, suggesting that veterans could help meet the growing demand for tech talent and artificial intelligence skills.
Keywords: J3; J4; J44; 330; military veterans; earnings levels and dispersion; work experience; licensing; public sector; occupation growth